Outcomes of 23- and 24-weeks gestation infants in Wellington, New Zealand: A single centre experience. Issue 1 (December 2017) - Berry, Mary; Saito-Benz, Maria; Gray, Clint; Dyson, Rebecca; Dellabarca, Paula; Ebmeier, Stefan; Foley, David; Elder, Dawn; Richardson, Vaughan
Abstract Optimal perinatal care of infants born less than 24 weeks gestation remains contentious due to uncertainty about the long-term neurodevelopment of resuscitated infants. Our aim was to determine the short-term mortality and major morbidity outcomes from a cohort of inborn infants born at 23 and 24 weeks gestation and to assess if these parameters differed significantly between infants born at 23 vs. 24 weeks gestation. We report survival rates at 2-year follow-up of 22/38 (58%) at 23 weeks gestation and 36/60 (60%) at 24 weeks gestation. Neuroanatomical injury at the time of discharge (IVH ≥ Grade 3 and/or PVL) occurred in in 3/23 (13%) and 1/40 (3%) of surviving 23 and 24 weeks gestation infants respectively. Rates of disability at 2 years corrected postnatal age were not different between infants born at 23 and 24 weeks gestation. We show evidence that with maximal perinatal care in a tertiary setting it is possible to achieve comparable rates of survival free of significant neuroanatomical injury or severe disability at age 2 in infants born at 23-week and 24-weeks gestation.